k-RAS mutations in non-small cell lung cancer patients treated with TKIs among smokers and non-smokers: a meta-analysis - Jiang, Ai-Gui; Lu, Hui-Yu (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Recent studies have suggested that k-RAS mutations are related to the response to epidermal growth factor receptor (EGFR) tyrosine-kinase inhibitions (TKIs) in advanced non-small cell lung cancer (NSCLC) treatment. The aim of this meta-analysis was to assess the relationship between smoking history and k-RAS mutations in NSCLC treated with TKIs. Material and methods : We searched MEDLINE and Web of Science up to 15 March 2014. The pooled relative risk (RR) was estimated by using fixed effect model or random effect model, according to heterogeneity between studies. We also carried out power analyses. Results : We identified 12 studies with 1193 patients, including 196 patients (16.4%) with k-RAS mutations. The pooled k-RAS mutations incidence was 22.8% (174/764) in patients with smoke expose vs. 5.4% (23/429) in those with no smoke exposure. The pooled RR was 2.991 (95% CI: 1.884–4.746; Z = 4.65, p = 0.000). No publication bias was found (Begg’s test: z = 1.09, p = 0.274 and Egger’s test: t = 1.38, p = 0.201). In subgroup analyses, the pooled RR was 3.336 (95% CI: 1.925–5.779; Z = 4.30, p = 0.000) in the Caucasian subgroup, while in the Asian subgroup the pooled RR was 2.093 (95% CI: 0.909–4.822; Z = 1.73, p = 0.083), but the sample size was underpowered (0.465). Conclusions : The current meta-analysis found that smoking was related to increased incidence of k-RAS mutations in non-small cell lung cancer treated with TKIs. This may be further evidence that smoking will lead to a worse prognosis in NSCLC patients treated with TKIs.